Forest Carbon Modeling in Poplar and Black Locust Short Rotation Coppice Plantation in Hungary - Mulyana, Budi; Polgár, András; Vityi, Andrea (Jurnal Sylva Lestari, 2024)
Forest carbon dynamic modeling for estimating the carbon stock in short rotation coppice bioenergy plantation in Hungary will be vital for better comprehending the role of black locust (Robinia pseudoacacia) and poplar (Populus sp.) in carbon dioxide sequestration from the atmosphere. The research aims were to estimate the potential carbon stock and describe the carbon distribution of the short rotation coppice bioenergy plantation above and below ground. Various sources were used to acquire parameterization data for developing forest carbon dynamic models. CO2FIX modeling V.3.2 was utilized in the data analysis to estimate the total carbon stock in biomass, soil, harvested wood products, and bioenergy compartments. Modeling has been around for 45 years. In this research, the total carbon stock of black locust and poplar at the end of the simulation period was 64.13 and 131.08 MgC.ha-1, respectively. The average carbon allocation above and below ground for black locust and poplar was 0.76, 19.76, 1.80, and 21.67 MgC.ha-1, respectively. In conclusion, poplar outperformed black locust regarding carbon storage in the short rotation coppice bioenergy plantation. Below ground carbon allocation was much higher than above ground. Therefore, more attention should be paid on below ground allocation through environmentally friendly soil management. Keywords: bioenergy plantation, carbon dynamics, climate change mitigation, CO2FIX model, fast growing species